VA‐ECMO‐assisted aspiration thrombectomy in a patient presenting with acute massive PE with absolute contraindications to thrombolytics. Issue 4 (8th July 2022) - Patel, Mit; Mujer, Mark; John, Alan; Darki, Amir
Abstract: Massive pulmonary embolism (PE) is a life‐threatening complication of major surgery with a mortality rate up to 50%. First‐line therapy for massive PE is systemic thrombolytics, but surgical patients are at high bleeding risk with absolute contraindications. As surgical thrombectomy carries a high burden of morbidity and mortality, endovascular interventions are becoming more common in these clinical scenarios. We report a case of a neurosurgical patient whose postoperative course was complicated by massive PE and subsequent cardiac arrest that required emergent venoarterial extracorporeal membrane oxygenation, followed by aspiration thrombectomy with the Inari FlowTriever Device (Inari Medical). The patient had immediate hemodynamic improvement with eventual recovery to baseline functional status.